Zig-Zag Run: Metode Latihan Kelincahan Tendangan Sabit Pencak Silat - Tofikin; Sinurat, Ridwan (UIR Press, 2020)
Method of training currently has not focused in improving physical conditions that can improve the ability of basic techniques of Pencak Silat. The purpose of this study was to determine the effect of zig-zag run training on the crescent-kick agility of Persaudraan Setia Hati Terate's Pencak Silat athletes. The type of research used experimental research, which is a type of research that is intended to seek the effect of certain treatments on others under controlled conditions. Experiments in this study are more pre-experimental types of pre-test and post-test in a group. The sampling technique used saturated samples with a sample amount of 19 athletes. The results showed that training of zig-zag run had an effect on the agility of the sickle kick in Setia Hati Terate Persaudaraan Pencak Silat athlete in Rokan Hulu Regency. From the results of the data analysis, the researcher recommends for the future study, namely the physical condition of the leg muscle explosive power and speed so that the agility of the sickle kick can be maximized.